Factors associated with adherence to antimicrobial stewardship after-hours - Mostaghim, M.; Snelling, Thomas; Bajorek, B. (John Wiley & Sons Ltd, 2018)
© 2018 Royal Pharmaceutical Society Objectives: Assess restricted antimicrobials acquired after standard working hours for adherence to antimicrobial stewardship (AMS) and identify factors associated with increased likelihood of adherence at the time of acquisition, and the next standard working day. Methods: All documented antimicrobials acquired from a paediatric hospital after-hours drug room from 1 July 2014 to 30 June 2015 were reconciled with records of AMS approval, and documented AMS review in the medical record. Key findings: Of the 758 antimicrobial acquisitions from the after-hours drug room, 62.3% were restricted. Only 29% were AMS adherent at the time of acquisition, 15% took place despite documented request for approval by a pharmacist. Antimicrobials for respiratory patients (OR 3.10, 95% CI 1.68–5.5) and antifungals (2.48, 95% CI 1.43–4.30) were more likely to be AMS adherent. Half of the acquisitions that required review the next standard working day were adherent to AMS (51.8%, 129/249). Weekday acquisitions (2.10, 95% CI 1.20–3.69) and those for patients in paediatric intensive care (2.26, 95% CI 1.07–4.79) were associated with AMS adherence. Interactions with pharmacists prior to acquisition did not change the likelihood of AMS adherence the next standard working day. Access to restricted antimicrobial held as routine ward stock did not change the likelihood of AMS adherence at the time of acquisition, or the next standard working day. Conclusion: Restricted antimicrobials acquired after-hours are not routinely AMS adherent at the time of acquisition or the next standard working day, limiting opportunities for AMS involvement.